An enterprise control assessment case study of the energy–water nexus for the ISO New England system. (May 2021) - Muhanji, Steffi Olesi; Barrows, Clayton; Macknick, Jordan; Farid, Amro M.
Abstract: The generation mix of Independent System Operator in New England (ISO-NE) is fundamentally changing. Nuclear, coal, and oil generation facilities are retiring and are replaced with natural gas, solar, and wind generation. Variable renewable energy resources (VREs) such as solar and wind present multiple operational challenges that require new and innovative ways to manage and control the grid. This paper studies how water supply systems (water and wastewater treatment), and water-dependent electricity generating resources (hydro, and thermal power plants) can be operated flexibly to enhance the reliability of the grid. The study's methodology employs the novel Electric Power Enterprise Control System (EPECS) simulator to study power systems operation, and the System-Level Generic Model (SGEM) to study water consumption and withdrawals. This work considers six potential 2040 scenarios for the ISO-NE energy–water nexus (EWN). It presents a holistic analysis that quantifies grid imbalances, normal operating reserves, energy market production costs, and water withdrawals and consumption. For scenarios with high amounts of VREs, the study shows great potential of water resources to enhance grid flexibility through improvements in load-following (up to 12.66%), and ramping (up to 18.35%) reserves. Flexible operation also results in up to 10.90% reduction in the total time VREs are curtailed. Additionally, flexible operation reduces water withdrawals by up to 25.58%, water consumption by up to 5.30%, and carbon dioxide emissions by up to 3.46%. In general, this work provides significant insights into how to jointly control the water and energy supply systems to aid in their synergistic integration. Highlights: A techno-economic control of energy–water resources for the ISO New England System. Curtailment of wind, solar and hydro resources to provide operating reserves. Demand-side management of energy–water resources improves grid flexibility. Flexible control of energy–water resources improves the environmental performance of the grid. Enterprise control case study results for the New England energy–water nexus.